Reversible-figure perception: Why is voluntary control limited?. (September 2022) - Toppino, Thomas C.
Observers can voluntarily avoid reversals of an ambiguous, reversible figure, extending the duration of an intended percept. This is usually attributed to high-level, top-down attentional processes. However, voluntary control is limited. Reversals occur despite attempts to avoid them. In two experiments, observers demonstrated significant, but limited, voluntary control over Necker cube perception. Cube size and cube completeness, variables associated with stimulus-driven processes involving neural adaptation, influenced the frequency of reversals regardless of observers' intentions. Results are consistent with the hybrid hypothesis that both top-down and bottom-up processes contribute to Necker-cube perception and support the hypothesis that the contribution of bottom-up processes is responsible for the limitation on voluntary control.